Rescue rebellion - Stilton, Geronimo (Stilton, Geronimo. Spacemice, 2015)
Traveling to the planet Jurassix to warn its inhabitants of an imminent comet strike, Geronimo Stilton and his crew encounter ferocious, dinosaur-like beasts who have an appetite for rodents.